The Effect of Giving Additional Feed Sente (Homalomena cordata scoot) on The Performance of Duroc Farming Pig - P., Yusadana; Budaarsa, K.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the effect of adding sente (Homalomena Cordata Scoot) in the ration on the performance of pigs. The study was carried out for 3 months in the race of pig farms in Delodceking Banjar, Lumbung Kauh Village, Selemadeg Barat District, Tabanan Regency. The design used was a randomized block design (RBD) consisting of 4 treatments 4 grup as a test. Four treatments were given, namely commercial ration (concentrate + rice bran) without sente (A) as control, commercial ration (concentrate + sente) 2% plus sente (B), commercial ration (concentrate + sente) 4% plus cente (C), 6% commercial ration (concentrate + rice bran) plus cente (D). The variables observed included initial body weight, final body weight, weight gain, feed consumption, FCR and the price of ration per 1 kg of the United Nations. The data obtained were analyzed by analysis of variance, if there were significantly different results (P <0.05) then followed by Duncans multiple distance test. The results showed that the addition of a commercial ration with a cente to a level of 6% gave a not significant effect on the performance of race pigs, but was able to decrease the cost of rations. Pigs which are maintained by giving commercial rations with the addition of 6% cente have a lower economic value compared to the control ration. Keywords: Commercial Ration, S ente (Homalomena Cordata Scoot) , Duroc Farming Pig